Pengaruh Penerapan Keselamatan dan Kesehatan Kerja (K3) Terhadap Produktivitas Kerja - Aditya Imam Wibisono; M. Agung Wibowo; Albani Musyafa (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
This research aims to analyze the influence of occupational safety on work productivity, the influence of occupational health on work productivity, the influence of occupational safety and health simultaneously on work productivity, as well as analyzing the dominant factors that influence the productivity of construction project workers. This research uses quantitative methods with multiple linear regression analysis. The population in this study were all employees and workers of the UGM FKKMK Microbiology Building Construction Project. The research results show that occupational safety and health have a partial or simultaneous effect on work productivity. The results of the dominant test analysis show that the occupational safety variable is more influential than the occupational health variable, namely 55.9%, while the occupational health variable is 45.9%.